2023
DOI: 10.3389/fneur.2023.1146194
|View full text |Cite
|
Sign up to set email alerts
|

Association between general anesthesia and contrast-induced encephalopathy after endovascular treatment on neurovascular diseases

Abstract: ObjectiveContrast-induced encephalopathy (CIE) is a rare neurological complication that can occur in the context of various endovascular procedures. Although many potential risk factors for CIE have been reported, it is still unclear whether anesthesia is a risk factor for the occurrence of CIE. The goal of this study was to investigate the incidence of CIE in patients who underwent endovascular treatment under different anesthesia methods and anesthetics administration and to explore whether general anesthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Stroke may disrupt the BBB within the same or adjacent vascular territory, promoting contrast leakage into broader brain regions and causing tissue reactions and brain edema. A recently published article indicated that general anesthesia could be a potential CIE risk factor [ 11 ]. The patient had no renal failure or chronic disease history in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke may disrupt the BBB within the same or adjacent vascular territory, promoting contrast leakage into broader brain regions and causing tissue reactions and brain edema. A recently published article indicated that general anesthesia could be a potential CIE risk factor [ 11 ]. The patient had no renal failure or chronic disease history in the present case.…”
Section: Discussionmentioning
confidence: 99%